2022
DOI: 10.1093/ijlct/ctac026
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer behavior in electrode and battery performance analysis of organic flow battery

Abstract: The organic flow battery is one of most potential electrochemical energy storage technologies due to the huge potential and cheap. The mass transfer performance is one of the main barriers to limit the development. The species distribution and transport process in the electrode is influenced by the geometric characteristic of electrode. A novel numerical model for the organic redox flow battery(ORFB) is built, and this model is verified by the experiments. The results show that the mass transfer and battery pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…(3) The electrolytes are incompressible. (4) The other irrelevant reactions have been ignored . (5) Only the hydrogen ions can pass through the ion-exchange membrane.…”
Section: Modelsmentioning
confidence: 99%
“…(3) The electrolytes are incompressible. (4) The other irrelevant reactions have been ignored . (5) Only the hydrogen ions can pass through the ion-exchange membrane.…”
Section: Modelsmentioning
confidence: 99%
“…7,8 z E-mail: yangyue@ncepu.edu.cn; yangga@mail.buct.edu.cn Journal of The Electrochemical Society, 2022 169 070529 It is well accepted that the performance of flow battery is influenced by the hydromechanics, transport and the species distribution in the electrode, all of which are dependent on the flow field and electrode design. 9,10 Therefore, the investigations about the multi-species transport process were paid much attention by the researchers in the past decades. 11,12 Wang et al 13 established a non-uniform numerical model of a VRFB and investigated the effect of electrode compression on the battery performance.…”
Section: List Of Symbolsmentioning
confidence: 99%
“…Thus, the study of mass transfer enhancement has become the focus to improve the performance of flow battery. [20][21][22] In our previous work, a new negative electrolyte(1-DPAQCl) [23] was synthesized, which can design a novel neutral ORFB by combining with positive electrolyte FcNCl. [24] For the novel electrolyte material, the way that hydrophilic groups substituted at β-sites (away from the ketones/carbonyl) can achieve more excellent water-miscibility than superseded at αsites (close to the ketones/carbonyl).…”
Section: Introductionmentioning
confidence: 99%
“…studied the effects of different electrode configurations on the battery voltages and mass transfer, which showed that sector electrode could enhance discharge voltage of organic redox flow battery, improve the active species distribution and suffer the best power‐based efficiency. Thus, the study of mass transfer enhancement has become the focus to improve the performance of flow battery [20–22] …”
Section: Introductionmentioning
confidence: 99%